EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Mardianto Mardianto; Siti Maysarah; Muhammad Iqbal-Nst (MES: Journal of Mathematics Education and Science, 2022)
This study aims to determine the mathematics learning outcomes students of class X MA Pondok Pesantren Darul Qur'an material linear equations before and after learning using Macromedia Flash learning media. The sample selection was through random sampling, the instrument used was in the form of tests conducted twice, namely before learning (pre-test) and after learning (post-test). The results of the data analysis requirements test, it is known that student learning outcomes are declared to be normally distributed and have variance homogeneous. The results showed that there were differences in students' mathematics learning outcomes before using macromedia flash learning media with an average of 57.1 and after using macromedia flash learning media, which was an average of 77.3. The results of data analysis using t-test showed there was a significant difference in improving students' mathematics learning outcomes. It can be concluded that the hypothesis is accepted where Macromedia Flash learning media is effectively used to improve students' mathematics learning outcomes in class X MA Pondok Pesantren Darul Qur'an in linear equation material.